2020
DOI: 10.1097/md.0000000000022838
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of patients with diabetic ketoacidosis of different severity

Abstract: To analyze the influencing factors and outcomes of the different severity of diabetic ketoacidosis (DKA). A total of 50 children with DKA admitted to the Department of Pediatrics, Tianjin Medical University General Hospital from January 2009 to December 2018 were included in this study. The patients were divided into mild group, moderate group, and severe group according to the severity of the disease. We then analyzed the clinical characteristics and outcomes of the 3 groups. Compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
4
0
5
Order By: Relevance
“…El TRC se define como el tiempo necesario hasta alcanzar una glucemia ≤200 mg/dl, HCO 3 ≥15mN, pH≥7.3 y AG≤12 mN. Al igual que en reportes previos, 13 , 14 el TRC en nuestro estudio fue mayor en aquellos pacientes con CAD severa. Evidenciamos una correlación negativa entre el TRC, pH, bicarbonato sérico y edad, y una correlación positiva con el recuento de glóbulos blancos, AG, potasemia y volumen de cristaloides utilizados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…El TRC se define como el tiempo necesario hasta alcanzar una glucemia ≤200 mg/dl, HCO 3 ≥15mN, pH≥7.3 y AG≤12 mN. Al igual que en reportes previos, 13 , 14 el TRC en nuestro estudio fue mayor en aquellos pacientes con CAD severa. Evidenciamos una correlación negativa entre el TRC, pH, bicarbonato sérico y edad, y una correlación positiva con el recuento de glóbulos blancos, AG, potasemia y volumen de cristaloides utilizados.…”
Section: Discussionunclassified
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18], siendo mayor en la CAD grave (Tabla 2). No hubo diferencias en el TRC según el tipo de DM ni el factor desencadenante.…”
unclassified
“…Ketoasidosis diabetikum (KAD) merupakan salah satu krisis hiperglikemik dan komplikasi akut yang paling umum terjadi pada penderita diabetes melitus (DM) (Dhatariya et al, 2020). KAD terjadi akibat defisiensi insulin absolut atau relatif yang bermanifestasi menjadi hiperglikemia, asidosis metabolik, ketosis, dan dehidrasi (Wei et al, 2020). American Diabetes Association (ADA) consensus tahun 2018 mengklasifikasikan KAD menjadi derajat ringan, sedang, dan berat berdasarkan keparahan asidosis metabolik dan status kesadaran.…”
Section: Pendahuluanunclassified
“…Perbedaan kadar kreatinin yang bermakna didapatkan pada dua dari tiga variasi antar derajat keparahan KAD, yaitu KAD derajat ringan dengan berat (p=0,043) dan KAD derajat sedang dengan berat (p=0,019). Hal ini didukung oleh Wei et al (2020) dan Wu et al (2020) dalam penelitiannya yang menghasilkan perbedaan bermakna dengan nilai kreatinin yang signifikan tinggi pada KAD derajat berat. Peningkatan kadar kreatinin serum menandakan penurunan volume darah dan hipoperfusi ginjal yang mencerminkan keparahan dehidrasi dan kerusakan organ tubuh, seperti pada ginjal yang kemudian dapat meningkatkan risiko AKI (Chen et al, 2020;Wei et al, 2020).…”
Section: Hasil Penelitianunclassified
“…Therefore, HB can be used as a biomarker of DKA. It has been reported that the HB is detected in sweat, serum, urine, , and tissue fluid . Clinically, the level of HB in serum is measured by a biochemical analyzer, which is time-consuming, laborious, invasive, and non-real-time detection .…”
Section: Introductionmentioning
confidence: 99%